2019
DOI: 10.3390/ijms20235970
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Insights into Innate Immunity Responding to Red Rot Disease in Red Alga Pyropia yezoensis

Abstract: Pyropia yezoensis, one of the most economically important marine algae, suffers from the biotic stress of the oomycete necrotrophic pathogen Pythium porphyrae. However, little is known about the molecular defensive mechanisms employed by Pyr. yezoensis during the infection process. In the present study, we defined three stages of red rot disease based on histopathological features and photosynthetic physiology. Transcriptomic analysis was carried out at different stages of infection to identify the genes relat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 93 publications
0
24
0
Order By: Relevance
“…In 2019, Im et al identified the genes involved in the interaction of the red alga Pyropia tenera and three pathogens using microarray analysis and histochemical methods [ 13 ]. Tang et al identified the genes associated with the defense response of the red alga Pyropia yezoensis against the necrotrophic pathogen Pythium porphyrae using transcriptomic analysis [ 14 ]. However, microalgal responses and defense reactions to pathogen infection at the molecular level have never been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Im et al identified the genes involved in the interaction of the red alga Pyropia tenera and three pathogens using microarray analysis and histochemical methods [ 13 ]. Tang et al identified the genes associated with the defense response of the red alga Pyropia yezoensis against the necrotrophic pathogen Pythium porphyrae using transcriptomic analysis [ 14 ]. However, microalgal responses and defense reactions to pathogen infection at the molecular level have never been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Pattern Recognition Receptors, including three lectin genes and a Toll/interleukin-1 receptor, were upregulated after infection. Expression of genes related to the ubiquitin-proteasome system and hypersensitive cell death, again reminiscent of plant effector-triggered immunity, increased significantly during the infection [ 153 ].…”
Section: Ecm Signaling and Innate Immunitymentioning
confidence: 99%
“…A family of potential microbe-sensing domains, specific of the Bangiophytes, was also identified, including C-lectins with Von Willebrand factor type A [ 7 ]. Several of these proteins were upregulated in Pyropia cultures infected by oomycetes [ 152 , 153 ]. Altogether, innate immunity in marine macroalgae consists of general constitutive defenses and genetic toolkits against specific pathogens [ 152 , 161 ].…”
Section: Ecm Signaling and Innate Immunitymentioning
confidence: 99%
“…Two pine TNL loci, TNL1 and TNL2, are correlated with blister rust resistance (Liu and Ekramoddoullah, 2011). TIR-domainencoding genes were more recently reported in the agriculturally important red algae, Pyropia yezoensis, which is used for nori production (Tang et al, 2019). At least one TIR-domain encoding gene, along with several NBS genes of Pyropia are upregulated by challenge with the oomycete pathogen, Pythium (Tang et al, 2019).…”
Section: Tir-proteins Across Plant Phylogeniesmentioning
confidence: 99%
“…TIR-domainencoding genes were more recently reported in the agriculturally important red algae, Pyropia yezoensis, which is used for nori production (Tang et al, 2019). At least one TIR-domain encoding gene, along with several NBS genes of Pyropia are upregulated by challenge with the oomycete pathogen, Pythium (Tang et al, 2019). Genes with TIR immune receptor-like domain combinations have been found in the genomes of green algae.…”
Section: Tir-proteins Across Plant Phylogeniesmentioning
confidence: 99%